Basalt Rock Powder in Cementitious Materials: A Systematic Review - Maryane Pipino Beraldo Almeida; Lays da Silva Sá Gomes; Alex Ramos Silva; Jacqueline Roberta Tamashiro; Fábio Friol Guedes Paiva; Lucas Henrique Pereira Silva; Angela Kinoshita (Resources, 2025)
Concrete and mortar production consumes significant natural resources, leading to environmental concerns and sustainability challenges. Sustainable alternatives, such as industrial byproducts, have been explored to replace clinkers and aggregates. Basalt rock powder (BRP) is a promising option due to its physical and chemical properties, including its better particle size distribution and compatibility with cementitious composites, and studies have highlighted its pozzolanic activity and its potential to improve mechanical properties (compressive strength, flexural strength, and durability). Reusing rock dust as a raw material could transform it into a mineral byproduct, benefiting the new material and reducing waste volumes. This article presents a systematic literature review on the use of BRP in construction materials, conducted using the Scopus, ScienceDirect, PubMed, and Web of Science databases and following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) procedures. The search resulted in 787 articles (up to December 2024) and, after the screening process, 17 met the inclusion criteria. From the selected articles, information regarding the utilization of this waste product; its influence on mechanical properties, pozzolanic activity, and durability; and the sustainability associated with its use was compiled. The risk of bias was low as the search was comprehensive, all the papers were peer-reviewed, and all authors reviewed the papers independently. In conclusion, the studies demonstrate the potential of using BRP as a component of cementitious materials, indicating it as a possible innovative solution to the current challenges in the construction industry.